Chapter Il «faticato peregrinaggio» di Isidoro Carini negli archivi e nelle biblioteche di Spagna (1881-1882) - CORRAO, Pietro (Reti Medievali E-Book, 2021)
The Relazione by Isidoro Carini about his research mission in Spain (1881-1882) and the events of its publication allow to reconstruct the beginnings of both the use of spanish sources for the Sicilian and Italian medieval history and of the context of the Sicilian medieval historiography at the end of the 19th Century.